Enhanced Model For Evaluating Information System Success: Determining Critical Criteria - Daghouri, A.; Mansouri, K.; Qbadou, M. (Engineering, Technology & Applied Science Research, 2018)
The purpose of this study is to enhance the DeLone and McLean information system success by adding a SERVQUAL instrument to evaluate the service quality dimension. An integrated model for evaluating the information system has been proposed. One of the most popular multi criteria decision making techniques, namely AHP was used to determine the weights of each criterion and sub-criterion of the model in order to identify the most influential criterion on information system’s evaluation. System quality dimension has a strong influence on information system success (0.39) followed by information quality (0.22). The proposed model could be used to enhance information system performance evaluation.